Red blood cells morphology and morphometry in adult, senior, and geriatricians dogs by optical and scanning electron microscopy - Montoya-Navarrete, Ana Luisa; Guerrero-Barrera, Alma Lilián; Quezada-Tristán, Teódulo; Valdivia-Flores, Arturo G.; Cano-Rábano, María J. (Frontiers in Veterinary Science, 2022)
Red blood cells (RBC) morphologic evaluation through microscopy optical (OM) and SEM, provides information to forecast, evaluate, and monitor the functioning of many organs. Factors, such aging and diseases affect RBC morphology in both, human and animals. SEM is useful to evaluate RBC morphology, although its use in diagnosis and evaluation in dogs is limited, due to the availability and cost. The aim of this research was to assess the normal RBC morphology in adult, senior and geriatrician dogs, clinically healthy by OM and SEM. In addition to evaluating the age effect, sex, body size, and their interaction on erythrocyte morphometry. To carry out the research 152 blood samples were evaluated from dogs of different sexes and body sizes (small, medium, and large). Three groups were made based on dogs age: group I adults (1 to 7.9 years old), group II senior (8 to 11.9 years old), and group III geriatricians (> 12 years old). Erythrocyte parameters were evaluated by OM (diameter, height, and axial ratio). Per each dog, the parameters of 20 erythrocytes were measured. A total of 2600 cells were scanned with the AmScope™ Software scale. In addition, the RBC morphology was evaluated by SEM. Statistical analyses used analysis of variance and a general linear model, which allows the comparison of multiple factors at two or more levels (p < 0.05). The results of this study showed that diameter and height were lower in adult dogs than in senior and geriatrician dogs (p < 0.05). Whereas sex, body size, and the interaction did not show a significant effect (p > 0.05). Additionally, some images of anisocytosis, polychromasia, and poikilocytosis (echinocytes, acanthocytes, codocytes, spherocytes, stomatocytes, dacryocytes quatrefoil, and elliptocytes) were obtained by OM and SEM. Our study provides information about the morphological and morphometry alterations of adult, senior and geriatrician dogs RBC. This work can contribute to motive the use of the dog as an experimental model in diseases that affect both humans and dogs, where it is necessary to evaluate the morphology of RBC.